Process integration study of biomass-to-methanol (via gasification) and methanol-to-olefins (MTO) processes in an existing steam cracker plant - Johansson, Erika (My University, 2013)
Ethylene and propylene, also referred to as light olefins, are important building blocks within the chemical industry and are used for the production of plastics. They are usually produced via steam cracking of naphtha or other light fractions of petroleum. This process route is a very energy consuming process and consumes non-renewable feedstock and will thus not be sustainable in the long run. Fossil feedstock can be replaced with biomass. Methanol is produced from biomass via gasification and methanol synthesis and then light olefins are produced in a Methanol-to-olefins (MTO) process. Replacing some of the olefins produced today via steam cracking at Borealis in Stenungsund with olefins produced via the MTO process is a first shift towards more sustainable production processes. The consequences of integrating the MTO process with the existing cracker plant as well as integrating the complete process chain from biomass to olefins with the existing cracker plant have been evaluated based on the potential for heat integration and the potential to produce high pressure steam. The potential for high pressure steam production is particularly relevant given the loss of high pressure steam production from the cracker furnaces when reducing their capacity. Energy- and mass balances were obtained by creating simulation models for the MTO process as well as the biomass to methanol process. The energy balances obtained were used as input data for a heat integration study using pinch analysis. The opportunities for heat integration with the existing cracker plant were evaluated for different cases. The first case was restricted to heat integration opportunities for the MTO process only. The second case included heat integration opportunities for the complete process chain from biomass to olefins. From the simulation models an energy yield from biomass to methanol of 0.51 MW/MW was obtained, which is similar to other published studies of this process. The yield going from methanol to olefins was based on yield data for the UOP/Hydro technology. The heat integration for the MTO and steam cracker case indicates that it is possible to transfer approximately 11.6 MW from the cracker process to the MTO process. Furthermore, it is possible to produce approximately 18 MW of high pressure steam from excess heat from the MTO process, which is not enough to cover the reduced production of high pressure steam from the cracking furnaces. In the biomass to olefins process, heat integration with the steam cracker shows opportunities to recover approximately 22 MW of process heat and produce 175 MW of high pressure steam, which would be enough to cover the loss in high pressure steam production.
Keywords: Energi; Kemiteknik; Hållbar utveckling; Energy; Chemical Engineering; Sustainable Development